Analisis Motivasi Kerja dalam Meningkatkan Kinerja Karyawan pada CV. Rizka Multidimensi - Amelia Retno Dwiyanti; Rizka Pangesti; Rini Sugiarti; Fendy Suhariadi (EduInovasi: Journal of Basic Educational Studies, 2025)
This research aims to analyze the role of work motivation in improving employee performance at CV. Multidimensional Rizka. A qualitative approach was used to explore influential motivational factors, involving in-depth interviews, observations and documentation studies. The research results show that appreciation, a conducive work environment, and emotional involvement with the company's vision are the main factors that influence employee motivation and performance. These findings provide practical recommendations for increasing employee motivation in order to achieve optimal productivity.